PATHOLOGICAL EFFECT OF TOXOCARA CANIS EGG DOSES IN EXPERIMENTAL MICE. - Hind J. Mahmood; Wisam M. Al-Saeed (Basrah Journal of Veterinary Research)
In this study we examined the effect of various sensitizing doses of infective Toxocara canis eggs and the trapping of larvae in different tissues of the murine host. The level of trapping increased with sensitization egg doses. Different doses of Toxocara canis eggs were given to ten groups each with five mice and then necropsied after different periods. Experimental toxocariasis in mice sacrificed at (1,2 and 3) weeks post infection showed no lesions in mice given 50, 75 and 100 Toxocara canis eggs respectively. Other groups given higher doses of T.canis eggs between (125-500 eggs) showed lesions in liver, lungs, eyes and muscles of sacrificed mice after 4 weeks of infection.